2019
DOI: 10.7759/cureus.4611
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus gordonii Empyema: A Rare Presentation of Streptococcus gordonii Infection

Abstract: Empyema is often caused by Streptococcus pneumoniae, Staphylococcus aureus, and a variety of gram-negative organisms as well as anaerobes. Streptococcus gordonii (S. gordonii) is among some of the initial colonizers of the periodontal environment that is recognized to cause bacterial endocarditis. However, there are only a few case reports of S. gordonii causing empyema in the literature. We report the case of a 75-year-old male who presented with coughing up blood-tinged sputum. Physical examination revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…[14][15][16] Hafsa Farooq et al reported a case of empyema caused by S gordonii infection. [17] Ziv Dadon et al reported 2 cases of spondylitis caused by S gordonii infections. [18] However, we have not found any cases of S gordonii finger infections in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Hafsa Farooq et al reported a case of empyema caused by S gordonii infection. [17] Ziv Dadon et al reported 2 cases of spondylitis caused by S gordonii infections. [18] However, we have not found any cases of S gordonii finger infections in the literature.…”
Section: Discussionmentioning
confidence: 99%